Tissue engineering and the future of hip cartilage, labrum and ligamentum teres. Issue 1 (11th August 2015) - Stubbs, Allston J.; Howse, Elizabeth A.; Mannava, Sandeep
Abstract : As the field of hip arthroscopy continues to evolve, the biological understanding of orthopaedic tissues, namely articular cartilage, labral fibro-cartilage and the ligamentum teres continues to expand. Similarly, the need for biological solutions for the pre-arthritic and early arthritic hip continues to be a challenge for the sports medicine surgeon and hip arthroscopist. This article outlines existing biological and tissue-engineering technologies, some being used in clinical practice and other technologies being developed, and how these biological and tissue-engineering principals may one day influence the practice of hip arthroscopy. This review of hip literature is specific to emerging biological technologies for the treatment of chondral defects, labral tears and ligamentum teres deficiency. Of note, not all of the technologies described in this article have been approved by the United States Food and Drug Administration and some of the described uses of the approved technologies should be considered 'off-label' uses.